Diagnostic and prognostic value of an ejection fraction adjusted for myocardial remodeling - Chan, Wei Xuan; Kaura, Amit; Mulla, Abdulrahim; Papadimitriou, Dimitri; Glampson, Benjamin; Mayer, Erik; Shah, Anoop S. V.; Mayet, Jamil; Yap, Choon Hwai (Frontiers in Cardiovascular Medicine, 2024)
Ejection fraction (EF) is widely used to evaluate heart function during heart failure (HF) due to its simplicity compared but it may misrepresent cardiac function during ventricular hypertrophy, especially in heart failure with preserved EF (HFpEF). To resolve this shortcoming, we evaluate a correction factor to EF, which is equivalent to computing EF at the mid-wall layer (without the need for mid-layer identification) rather than at the endocardial surface, and thus better complements other complex metrics. The retrospective cohort data was studied, consisting of 2752 individuals (56.5% male, age 69.3±16.4 years) admitted with a request of a troponin test and undergoing echocardiography as part of their clinical assessment across three centres. Cox-proportional regression models were constructed to compare the adjusted EF (EFa) to EF in evaluating risk of heart failure admissions. Comparing HFpEF patients to non-HF cases, there was no significant difference in EF (62.3±7.6% versus 64.2±6.2%, p=0.79), but there was a significant difference in EFa (56.6±6.4% versus 61.8±9.9%, p=0.0007). Both low EF and low EFa were associated with a high HF readmission risk. However, in the cohort with a normal EF (EF≥50%), models using EFa were significantly more associative with HF readmissions within 3 years, where the leave one out cross validation ROC analysis showed a 18.6% reduction in errors, and Net Classification Index (NRI) analysis showed that risk increment classification of events increased by 12.2%, while risk decrement classification of non-events decreased by 16.6%.EFa is associated with HF readmission in patients with a normal EF.